CONSUMER ETHNOCENTRISM AND LIFESTYLES OF MEMBERS OF THE DEFENSE SYSTEM - (Ilić) Petrovic, Jelena R; Radovi', Kristina (The Policy of National Security, 2025)
Consumer ethnocentrism is a form of economic patriotism and awareness of the significance of buying local products to develop the domestic economy. Since consumer habits are closely linked with consumers’ lifestyles, and that lifestyles, besides socio-demographic aspects, represent an important determinant of consumer market behaviour, this paper aims to determine whether there are differences in consumer ethnocentrism and lifestyles of members of the defence system compared to the civilian population. The research included 180 respondents in total, members of the Ministry of Defense and the Serbian Armed Forces, and civilians employed in other fields of the economy. Independent variables defined in the research were gender, education, generational affiliation, and belonging to the defense system, while dependent variables were the scores on the consumer ethnocentrism and lifestyle preferences subscales. The data was processed with the help of descriptive statistics, t-tests for independent samples, and linear regressions. The results show differences in preferences of specific lifestyles between members of the defense sector and civilians, but not in consumer ethnocentrism. There are also statistically significant differences regarding consumer ethnocentrism and lifestyle preferences regarding socio-demographic variables. Moreover, even the preferences of specific lifestyles, as a form of consumer behavior, have been shown as statistically significant predictors of consumer ethnocentrism. Therefore, it is only justified to dedicate more attention to future research to examine the lifestyles and consumer habits of specific groups of inhabitants to raise their awareness of the importance of purchasing domestic products to strengthen the domestic economy.
Keywords: consumer behavior; military; Serbia; values; lifestyles; Millennials; Generation Z